2020
DOI: 10.37939/jrmc.v24i2.1232
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children with Epilepsy in Wah Cantt, Pakistan: A Cross-sectional Study

Abstract: Objective: To assess the Quality Of Life (QOL) in children with epilepsy using modified QOLCE-55 questionnaire. Material and Methods: We consecutively enrolled children aged 4 to 16 years who were under treatment for childhood epilepsy. Basic demographic and clinical details including type of epilepsy, developmental history, family history of epilepsy and any co-morbidity were recorded in a predesigned Performa. QOL was evaluated by using modified QOLCE-55 (39 items) from parents. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…reported this finding in the 12-15-year age group [ 21 ]. Moreover, Shetty et al [ 22 ] and Ohaeri et al [ 23 ] showed more significant associations when older age groups had lower scores of physical pain, emotional health, and memory and language QoL; however, they observed this finding in an adult population unlike our pediatric participants, which may support the hypothesis that being burdened by the disease and its stigma for a longer period and exhaustion of caretakers leads to a decline in several domains in QoL.…”
Section: Discussioncontrasting
confidence: 46%
“…reported this finding in the 12-15-year age group [ 21 ]. Moreover, Shetty et al [ 22 ] and Ohaeri et al [ 23 ] showed more significant associations when older age groups had lower scores of physical pain, emotional health, and memory and language QoL; however, they observed this finding in an adult population unlike our pediatric participants, which may support the hypothesis that being burdened by the disease and its stigma for a longer period and exhaustion of caretakers leads to a decline in several domains in QoL.…”
Section: Discussioncontrasting
confidence: 46%
“…[ 27 ] Some of the published literature revealed that females are found to have poorer QOL than males. [ 23 28 ] In the current study, associations of the QOL domain scores with the predictors revealed that gender was significantly associated with the social domain, and the total score of QOL where males were significantly associated with a better QOL. In a study that showed the correlation between epilepsy and school attendance, females had a higher percentage of absenteeism.…”
Section: Discussionmentioning
confidence: 50%
“…Srujna et al [ 11 ] observed that gender and age of participants had no relation to the QOL, but factors, such as maternal education and socioeconomic status, strongly correlated with QOL. Haider et al [ 6 ] observed that the type of epilepsy had no relation to QOL, but the patient's age and gender affected QOL. In contrast to other studies, such as Nadkarni et al [ 10 ], they observed that the QOL was more affected in older children with lower socioeconomic status and mothers with lower literacy levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the diagnosis of a chronic illness, such as epilepsy, during childhood is a source of severe stress and poor QOL for the whole family, including parents and siblings [4]. Although few Indian studies [5][6][7][8][9][10][11] have tried to ascertain the QOL of children with epilepsy, there are limited studies on how pediatric epilepsy impacts the QOL of siblings [12][13][14][15]. Hence, we have attempted to assess the QOL of children with epilepsy using epilepsy-specific questionnaires Quality of Life in Childhood Epilepsy Questionnaire-55 (QOLCE-55) and Pediatric Quality of Life Epilepsy Module (Peds QL EM), and the QOL of their siblings was evaluated using the Peds QL Inventory.…”
Section: Introductionmentioning
confidence: 99%